2012
DOI: 10.1016/j.pbb.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Lack of efficacy of curcumin on neurodegeneration in the mouse model of Niemann–Pick C1

Abstract: In order to determine the efficacy of curcumin in ameliorating symptoms of neurodegeneration in the mouse model of Niemann–Pick C1, a variety of formulations and dosages of curcumin, one comparable to one previously reported as efficacious, were provided orally to Npc1−/−mice. Plasma levels of curcumin, survival, tests of motor performance, and memory (in some cases) were performed. We found variable, but mild, increases in survival (1.5% to 18%). The greatest increased survival occurred with the highest dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
1
20
0
1
Order By: Relevance
“…These studies have largely had limited effect on the NPC disease phenotype. The compounds that have been examined include statin drugs (lovastatin and pravastatin) [28][29][30], a squalene synthesis inhibitor (CP-340868) [31], cholestyramine [28,29], nicotinic acid [28], ezetimibe (Zetia) [32], peroxisomal inducers (clofibrate, perfluorooctanoic acid, dehydroepiandrosterone, and diethylhexylphthalate) [33,34], neurosteroids or their mimics (allopregnanolone, ganaxolone, and T-0901317) [35,36], oxysterols (25-and 27-hydroxycholesterol, 7-ketocholesterol, and 17b-estradiol) [17,[37][38][39][40], synthetic liver X receptor ligands (T-0901317 and bexarotene) [40][41][42][43], sphingolipid pathwaytargeting agents (miglustat and n -butyldeoxygalactonojirimycin) [44][45][46], calcium regulators (curcumin, thapsigargin, and myriocin; note that curcumin is also an HDACi) [47][48][49], apoptosis inhibitors (imatinib, minocycline, and B-cell lymphoma 2 protein) [50,51], a neurodegeneration inhibitor (N ω -nitro-L-arginine methyl ester) [52], α-tocopherol (vitamin E) [53,54], tamoxifen [53], nitrovin (difurazone) [55], and several members of 3 heterocycle series consisting of highly substituted pyrrolinones, triazines, and thiadiazoles [56][57][58][59]. Low cholesterol diets have been found to be ineffective …”
Section: Therapies Tested Previously For Treatment Of Npc Diseasementioning
confidence: 99%
“…These studies have largely had limited effect on the NPC disease phenotype. The compounds that have been examined include statin drugs (lovastatin and pravastatin) [28][29][30], a squalene synthesis inhibitor (CP-340868) [31], cholestyramine [28,29], nicotinic acid [28], ezetimibe (Zetia) [32], peroxisomal inducers (clofibrate, perfluorooctanoic acid, dehydroepiandrosterone, and diethylhexylphthalate) [33,34], neurosteroids or their mimics (allopregnanolone, ganaxolone, and T-0901317) [35,36], oxysterols (25-and 27-hydroxycholesterol, 7-ketocholesterol, and 17b-estradiol) [17,[37][38][39][40], synthetic liver X receptor ligands (T-0901317 and bexarotene) [40][41][42][43], sphingolipid pathwaytargeting agents (miglustat and n -butyldeoxygalactonojirimycin) [44][45][46], calcium regulators (curcumin, thapsigargin, and myriocin; note that curcumin is also an HDACi) [47][48][49], apoptosis inhibitors (imatinib, minocycline, and B-cell lymphoma 2 protein) [50,51], a neurodegeneration inhibitor (N ω -nitro-L-arginine methyl ester) [52], α-tocopherol (vitamin E) [53,54], tamoxifen [53], nitrovin (difurazone) [55], and several members of 3 heterocycle series consisting of highly substituted pyrrolinones, triazines, and thiadiazoles [56][57][58][59]. Low cholesterol diets have been found to be ineffective …”
Section: Therapies Tested Previously For Treatment Of Npc Diseasementioning
confidence: 99%
“…(Ferrante, et al, 2003;Hockly, et al, 2003). The extensions of survival fall in the class of what tamoxifen and vitamin E accomplished (expressed in failures of weight gain which translates into about a 3-fold greater survival; Bascunan-Castillo, et al, 2004) and are significantly better than curcumin's effect (barely significant in our hands; Borbon, et al, 2012). However, it is far less than what treatment with hydroxypropyl-beta-cyclodextrin, especially when delivered intrathecally, accomplishes (Liu, et al, 2009).…”
Section: Resultsmentioning
confidence: 92%
“…In the meantime, various common medications and/or food additives may ameliorate symptoms. The anti-inflammatory agents ibuprofen (Smith, et al, 2009) andvitamin E (Bascunan-Castillo, et al, 2004;Xu, et al, 2009) have been beneficial in animal models while curcumin has not much (Borbon, et al, 2012). Recently, histone deacetylase (HDAC) inhibitors have been proposed as drugs for the disease (Pipalia, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies suggested the lack of curcumin's efficiency in preventing neurodegeneration in mice [Borbon et al 2012].…”
Section: Other Therapeutic Compounds With No Established Benefit and mentioning
confidence: 97%